An overview of the spark plug engine profile in a spark ignition engine - Azrin, Abdul Aziz; Muhammad Yusri, Ismail; K., Sudhakar; C W, Mohd Nor; A, Zainal; Anwar, P. P. Abdul Majeed (IOP Publishing, 2021)
The main concern regarding on the spark plug usage is their ignition efficiency and lifetime capabilities. This article reviews on the spark plug engine profile in a spark ignition. An intelligent practical approach needs to be developed to be the indicator to know when the spark plug should be changed. Due to its promising effect on the spark ignition engine, the study of spark plugs profile is increasing day by day. For safety, mechanical vibration of a vehicle is a very important phenomenon. Moreover, it specifically affects passenger comfort in some applications. Due to the effects on vehicle structure components and passenger comfort as well as safety, the mechanical vibration through the spark ignition engine has acquired great significance. However, there are many problems in researching existing running engines with a spark ignition system, such as slower ignition, increased cyclic variance and possible misfire. The higher spark energy will improve the ignitibility, but due to electrode corrosion, the life of the spark plug will decrease, and electrodes serve as a sink of thermal energy that will affect the spark plug’s health. For instance, the conditions such as the spark plug gap, the plug thickness and the carbon dissipated on the spark plug that influences the output of a spark ignition, are highlighted in this article.